Climate change and forest restoration in Extreme South of Bahia: empirical study of legal reserve in rural properties - Fernandes Corrêa , Fábio; Rahnemay Rabbani, Roberto Muhájir; Carregosa Rabbani, Allívia Rouse (Brazilian Journal of Agroecology and Sustainability, 2024)
Climate change emerges as one of the most urgent and complex challenges humanity faces in the 21st century. In this context, promoting effective public policies and enacting legislation becomes imperative to mitigate adverse impacts and adapt societies to new environmental dynamics. These policies play a pivotal role in orchestrating efforts toward a more sustainable and resilient economy, providing an essential legal framework to guide individual, collective, and governmental actions toward climate change mitigation. Brazil has committed itself to restore 12 million hectares of forests by 2030 as one of the strategies to mitigate climate change. Even though the 20-year period for restoring the legal reserve is established, the initial time frame is not expressly provided by law, which has led to inconsistencies and possible low effectiveness of forest management policies. This study verified rural environmental registries (CAR in Portuguese) of properties in the State of Bahia and analyzed restoration timetables for legal reserve area. The results show that in 70,59% of the properties, which need to restore the legal reserve, the timetable extrapolated the year 2032. In 45% of them, the term was counted from the registration of the rural property in the CAR. It was concluded that the mistaken interpretations adopted weaken the recovery of native vegetation and, to a greater extent, the Brazilian goal of forest restoration by 2030.